A 1-bit 16×16 reconfigurable intelligent surfaces array for C-band - Zhang, Yucheng (Nanyang Technological University, 2025)
Reconfigurable Intelligent Surfaces (RIS) are the recent essential technologies to achieve the goal of manipulating electromagnetic waves for transmissions and reflections of signals. Their characteristics make them a promising technique which could improve the performance of mobile communication systems especially for 5G and 6G communications. RIS array is achieved by combining a number of basic elements together with PIN diodes which control the on and off state of RIS units. Through specific calculation of algorithm, arrangement of RIS array used for different target direction with different composed number of RIS units could be figured out. Adjustments of RIS array then could be applied to realize the goal of beamforming to certain users. This dissertation investigates a 1-bit RIS array for electromagnetic wave manipulation in C-band. The method uses a 16×16 RIS array, with each element being controlled by PIN diodes to dynamically switch states for precise phase adjustments. By implementing a beamforming algorithm using MATLAB, the system controls the RIS array to reflect signals in targeted directions. Simulation results validate the effectiveness of this RIS array design in enhancing communication performance. The findings underscore the potential of RIS technology to achieve energy-efficient, high-performance wireless communication networks.